Cognitive Effort in Text Processing and Reading Comprehension in Print and on Tablet: An Eye-Tracking Study. Issue 4 (21st April 2022) - Delgado, Pablo; Salmerón, Ladislao
ABSTRACT: In the present article, we examined the effect of the reading medium and the reading time-frame on text processing, metacognitive monitoring of comprehension, and comprehension outcomes. The eye movements of 116 undergraduates were recorded while they read three texts in print and three texts on a tablet under self-paced reading time or under time pressure. After each text, participants predicted their performance on a subsequent text comprehension test (i.e., an indicator of metacognitive monitoring). Overall, the results showed that participant performed similarly across media in all the reading processes evaluated, regardless of the reading time-frame. The only significant difference indicated that participants fixated more on text titles when reading in print than on the tablet. Although comprehension scores were slightly higher when reading in print, the difference only approached significance. The findings adhere to recent evidence suggesting that the in-print reading superiority is negligible when reading on tablets, as compared to reading on computers.